Identification of Histamine producing enterobacteriaceae in Indian mackerel (Rastrelliger kanagurta) using Polymerase Chain Reaction - Menaka, S.; Ginigaddarage, P.H.; Ariyawansa, K.W.S.; Jayasinghe, C.V.L. (Faculty of Arts, University of Jaffna, 2016)
Fish is vital source of protein consumed by the world’s population. Fresh fish flesh is the most common source of high protein food and an important source of protein in human nutrition in Sri Lanka. Not only as a food but also it has a substantial social and economic importance. The major unavoidable problem facing by the sea food industries in Sri Lanka is the rapid spoilage of fish before delivering it to consumers. Fish may harbor a number of biohazards as well as chemical contaminations such as biogenic amines and pathogenic microorganisms. Histamine is formed by free histidine available in large amount in the fish belonging to the scombridae family with the action of histidine decarboxylase enzyme. Gram negative enterobacteriaceae family microorganisms involve in histamine spoilage of fish and fish products. Rapid detection of histamine forming microorganisms is essential to ensure the product safety and minimize the product loss in the market. In this study of detection of histamine producing enterobacteriaceae family microorganisms, Indian mackerel (Rastrelliger kanagurta) collected from local markets were diluted in Maximum Recovery Diluent (MRD) and colonies were grown on Violet red Bile Glucose Agar (VRBG). Various sizes of colonies were used in Polymerase Chain Reaction (PCR) and positive results for the hdc gene which is responsible for the histamine formation was obtained in 36 isolates out of 163 tested. From PCR, Gram staining and biochemical test Enterobacter spp , Klebsiella spp ,Proteus spp and Morganella morgini were identified as histamine producing enterobacteriaceae in Indian mackerel
Keywords: Enterobacteriaceae; Fish; Histamine; hdc; Polymerase chain reaction